From Educators, For Educators - Cynthia Demetriou; Debra Hrelic (Journal of Effective Teaching in Higher Education)
Educator stress, burn-out and fatigue greatly affect faculty success and retention. The purpose of this research was to increase understanding of the lived experiences of educators and identify tangible strategies to help them thrive in higher education. Using an online open-ended cross-sectional survey and content analysis, this study explored qualitative data regarding nursing faculty experiences of stress, changes in pedagogy, and peer-to-peer faculty advice. Findings from 113 participants highlight recommendations from and for educators including pedagogical approaches as well as insights on compassion, compassion-fatigue, and self-compassion. Educator experiences are shared with the hope that faculty will use peer guidance to reflect on their own activities, make enhancements, and enact change.